Pengaruh Praktik Good Corporate Governance Terhadap Praktik Manajemen Laba (Studi Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2013-2017) - Rahma Febrina; Ulfi Maryati; Ferdawati (Akuntansi dan Manajemen, 2018)
Financial reports are a medium for companies to convey information about the accountability of management to the needs of external parties. Earnings management is a deliberate process of taking steps within the limits of general accounting principles both inside and outside the limits. This study aims to analyze the influence of good corporate governance consisting of independent board of directors, managerial ownership and institutional ownership on earnings management by using modified jones models with proxy discretionary accruals. The sample used was a banking company listing in the Indonesia Stock Exchange in the 2013-2017 period using purposive sampling with a sample of 22 companies and analyzed by multiple regression. The results of this study state that partially that the independent board of directors affects earnings management in a positive direction, while managerial ownership and institutional ownership do not affect earnings management. Simultaneously the board of commissioners, independent board of directors, managerial ownership and institutional ownership have no significant effect on earnings management.